2019
DOI: 10.1111/pde.14006
|View full text |Cite
|
Sign up to set email alerts
|

Hamartomas and midline anomalies in association with infantile hemangiomas, PHACE, and LUMBAR syndromes

Abstract: Background/Objective: The pathogenesis of infantile hemangiomas (IH), PHACE, and LUMBAR syndromes remains unknown. We aim to describe histopathologic features of midline anomalies associated with IH, including patients with PHACE and LUMBAR syndromes. Methods: A multicenter retrospective chart review was performed to identify patients with IH, PHACE, and LUMBAR syndrome with histopathologic specimens from sternal or midline anomalies. A total of 18 midline lesions from 13 patients were included. Out of 18, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…RMH cases may also be associated with congenital anomalies. 2,3638 RMH is superficially located and characterized by groups of mature skeletal muscle oriented perpendicular to the surface epithelium along with adipose and adnexal structures and occasionally blood vessels and nerves. 1 Depending on the clinical context and degree of skeletal maturation, the differential diagnosis for RMH may include both fetal rhabdomyoma and embryonal RMS.…”
Section: Discussionmentioning
confidence: 99%
“…RMH cases may also be associated with congenital anomalies. 2,3638 RMH is superficially located and characterized by groups of mature skeletal muscle oriented perpendicular to the surface epithelium along with adipose and adnexal structures and occasionally blood vessels and nerves. 1 Depending on the clinical context and degree of skeletal maturation, the differential diagnosis for RMH may include both fetal rhabdomyoma and embryonal RMS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar genetic abnormalities might be responsible for RMH in humans. A recent study showed the relation between aberration of mesenchymal cells during development and RMH 14 . Watchful waiting is recommended; however, surgery can be done.…”
Section: Discussionmentioning
confidence: 99%
“…Of these congenital RMHs, 23% (n = 11) were associated with congenital anomalies 2 . A wide variety of congenital anomalies have been reported with RMH and include amniotic band syndrome, 1,3 cleft lip or palate defects, 1,3 auricular anomalies, 4 ocular anomalies, 3,4 dermoid cyst, 5 thyroglossal duct sinus or cyst, 6 spinal dysraphism, 7 infantile hemangiomas, 3 LUMBAR, 7 and PHACE syndromes 8 …”
Section: Discussionmentioning
confidence: 99%
“…2 A wide variety of congenital anomalies have been reported with RMH and include amniotic band syndrome, 1,3 cleft lip or palate defects, 1,3 auricular anomalies, 4 ocular anomalies, 3,4 dermoid cyst, 5 thyroglossal duct sinus or cyst, 6 spinal dysraphism, 7 infantile hemangiomas, 3 LUMBAR, 7 and PHACE syndromes. 8 Midline congenital lesions of the head, neck, and chest include a broad differential. Thyroglossal cysts typically present on the midline neck and have the potential to communicate with the base of the tongue or the pharynx, causing movement with swallowing.…”
Section: Discussionmentioning
confidence: 99%